An integrated map of human chromosome 6p23. - Olavesen, MG; Davies, A; Broxholme, S; Wixon, J; Senger, G; Nizetic, D; Campbell, R; Ragoussis, J (1995)
The human chromosomal band 6p23 is a Giemsa-negative (light) band that may be expected to be relatively gene rich. The genes for spinocerebellar ataxia type 1 (SCA1), guanosine monophosphate reductase (GMPR), DEK involved in a subtype of acute myeloid leukemia (AML), and the folate-sensitive fragile site FRA6A, have already been mapped to 6p23. Recent linkage data have suggested evidence for a susceptibility locus for schizophrenia in the region. We have constructed a single YAC contig of approximately 100 clones spanning the entire 6p23 band from 6p22.3 to 6p24.1 and covering 7.5-8.5 Mb of DNA. The YAC contig contains 55 markers including genetically mapped STSs, physically mapped STSs, anonymous STSs, anonymous ESTs, and ESTs from the genes mapped to the region. The order of the genetically mapped STSs is consistent with their order in the contig and some of the markers not resolved on the genetic map have been resolved by the YACs. Four of the YACs from 6p23 and covering approximately 3 Mb of DNA have been used to isolate approximately 300 cosmids from a flow-sorted human chromosome 6 cosmid library, which have been organized into pockets. The proposed susceptibility locus for schizophrenia is most closely linked to D6S260, which is located within the YAC contig along with genetic markers < or = 5 cM on either side. Therefore, the presented materials are valuable reagents for characterization of the genomic region implicated in schizophrenia.